Intervention with isoleucine or valine corrects hyperinsulinemia and reduces intrahepatic diacylglycerols, liver steatosis, and inflammation in Ldlr−/−.Leiden mice with manifest obesity‐associated NASH. Issue 8 (13th July 2022) - Gart, Eveline; van Duyvenvoorde, Wim; Caspers, Martien P. M.; van Trigt, Nikki; Snabel, Jessica; Menke, Aswin; Keijer, Jaap; Salic, Kanita; Morrison, Martine C.; Kleemann, Robert
Abstract: Non‐alcoholic steatohepatitis (NASH) is associated with a disturbed metabolism in liver, insulin resistance, and excessive accumulation of ectopic fat. Branched‐chain amino acids (BCAAs) may beneficially modulate hepatic lipids, however, it remains unclear whether individual BCAAs can attenuate already established NASH and associated oxidative‐inflammatory stress. After a 26 weeks run‐in on fast food diet (FFD), obese Ldlr−/−.Leiden mice were treated for another 12 weeks with either valine or isoleucine (3% of FFD) and then compared to FFD controls. Valine and isoleucine did not affect obesity, dyslipidemia, gut permeability, or fecal fatty acid excretion, but significantly reduced hyperinsulinemia. Valine and isoleucine reduced ALT, CK18‐M30, and liver steatosis with a particularly pronounced suppression of the microvesicular component (−61% by valine and −71% by isoleucine). Both BCAAs decreased intrahepatic diacylglycerols and 4‐hydroxynonenal immunoreactivity, a marker for oxidative stress‐induced lipid peroxidation. Functional genomics analysis demonstrated that valine and isoleucine affected BCAA metabolism genes, deactivated master regulators of anabolic pathways related to steatosis (e.g., SREBPF1), and activated master regulators of mitochondrial biogenesis (e.g., PPARGC1A) and lipid catabolism (e.g., ACOX1, AMPK). This correction of critical metabolic pathways on gene expression level was accompanied by a significant decrease in histological liver inflammation, and suppression of FFD‐stimulated cytokine and chemokine proteins KC/CXCL1, MCP‐1/CCL2, and MIP‐2/CXCL2 and their pathways. In conclusion, dietary intervention with either valine or isoleucine corrected liver diacylglycerols, gene expression of multiple metabolic processes, and reduced NASH histology with profound hepatoprotective effects on oxidative stress and inflammatory proteins.